Mali : Technical Assistance Report. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2015)
This Technical Assistance Report surveys the resources of the subnational jurisdictions and proposes a tax reform strategy for Mali. In Mali, the system of local taxes generates insufficient revenue and relies on obsolete taxes, which are particularly difficult to collect. It proposes that the rental value be replaced by a value per hectare indexed on various factors such as access to property or public services; geographic location; and average and georeferenced consumption of electricity, water, cell phone minutes. A real property tax system will also require the elimination of key exemptions under the current real property tax.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet